Immunotherapy in Penile Squamous Cell Carcinoma: Present or Future? Multi-Target Analysis of Programmed Cell Death Ligand 1 Expression and Microsatellite Instability - Montella, Marco; Sabetta, Rosalaura; Ronchi, Andrea; De Sio, Marco; Arcaniolo, Davide; De Vita, Ferdinando; Tirino, Giuseppe; Caputo, Alessandro; D’Antonio, Antonio; Fiorentino, Francesco; Facchini, Gaetano; Lauro, Giovanni Di; et al. (Frontiers in Medicine, 2022)
Background: Penile Carcinoma (PC) is an extremely rare malignancy and the patients at advanced stages have currently limited treatment options with disappointing results. Immune checkpoint inhibitors anti-programmed cell death 1 (PD-1)/programmed cell death ligand 1 (PD-L1) are currently changing the treatment of several tumors. Furthermore, the microsatellite instability (MSI) and the deficient of mismatch-repair-system- (dMMR) proteins represent predictive biomarkers for response to immune checkpoint therapy. To date, few data have been reported related to PD-L1 expression and MSI in PC. The main aim of our study was the evaluation of PD-L1 expression in tumor cells and tumor-infiltrating immune cells (TILs) and the analysis of dMMR/MSI status in a large series of PCs. Methods: A series of 72 PC, including 65 usual squamous cell carcinoma (USCC), 1 verrucous, 4 basaloid, 1 warty and 1 mixed (warty-basaloid) was collected. Immunohistochemistry was performed to assess PD-L1 expression using two different anti-PD-L1 antibodies (clone SP263 and SP142 Ventana) and MMR proteins expression using anti-MLH1, anti-PMS2, anti-MSH2 and anti-MSH6 antibodies. PCR analysis was performed for the detection of MSI status. Results: Of the 72 PC cases analyzed by IHC, 45 (62.5%) cases were TCS positive and 57 (79%) cases CPS positive using PDL1 SP263. In our cohort, TILs were present in 62/72 (86.1%), 47 (75.8%) out of 62 cases showed positivity to PDL1 clone SP142. In our series, 59 cases (82%) were pMMR, 12 cases (16.7%) lo-paMMR and only 1 case (1.3%) MMR. PCR results showed that only one case lo-paMMR was MSI-H and the case dMMR by IHC not confirmed MSI status. Conclusions: Our findings showed that PD-L1 expression and MSI status represent frequent biological events in this tumor suggesting a rationale for a new frontier in the treatment of PC patients based on the immune checkpoint inhibitors.